A Review of Defense Mechanisms against Distributed Denial-of-Service (DDoS) Attacks on the Application Layer, as well as Machine Learning (ML)-based Mechanisms to Defend Against DDoS Attacks - Dharmesh Dhangar (International Journal of Intelligent Systems and Applications in Engineering, 2024)
DoS attacks at the application layer are made possible by flaws in the implementation or design of protocols. In contrast to volumetric DoS attacks, these assaults are covert and aim at a particular program that is currently running on the victim. Numerous attacks on commonly used protocols at the application level have been discovered in recent years. In this paper, we provide a structured and thorough review of current application-level DoS risks and ways to mitigate them. Existing attacks and defenses are broken down into distinct groups, detailed in-depth, and contrasted using significant indicators of performance. The paper ends with suggestions for additional research.